THE APPLICATION OF ALTMAN’S Z-SCORE MODEL IN PREDICTING THE BANKRUPTCY POTENTIAL (Case study: Telecommunication Companies on the IDX 2013-2017) - Dadung, Herald Evaristo; Tulung, Joy Elly (Universitas Sam Ratulangi, 2018)
Abstract: Financial problem in a company is one of the factors that have an impact on bankruptcy potential. This study is aimed to estimate the likelihood of bankruptcy of Telecommunication companies listed on the Indonesia Stock Exchange for the period of 2013-2017. This study used quantitative descriptive research method where this research describes and measures the financial condition of telecommunication companies without seeking a relationship or influence of one company to another. The results show that there are three out of four telecommunication companies on the IDX are predicted to be in the Distress Zone or in other words potentially bankrupt. The three companies are PT. XL Axiata, Tbk in 2015 to 2017; PT. Indosat, Tbk from 2013 to 2016; and PT. Smartfren Telecom, Tbk from 2013 to 2017. Recommendation which can be given for those telecommunication companies that get Z-Score results in the distress zone or even in the gray zone is they can make this research result as an early warning so that they can take precautions before the occurrence of financial difficulties in the future that potentially lead to bankruptcy.Â Keywords: bankruptcy, altmanâ€™s z-score, financial distress, telecommunication companies.